PERSPEKTIF DEWASA MENURUT HUKUM ADAT SUKU DAWAN - Un, Alicia Chalista; Jacob, Yossie M Y; Bire, Chatryen M Dju; Ndolu, Juliana S (Petitum Law Journal, 2025)
The determination of a person's maturity as a legal subject fundamentally affects their ability to act according to the law. The criteria for adulthood serve as one of the determinants of legal capacity, which is explicitly stated in Article 1330 of the Civil Code. Therefore, positive law provides a specific age benchmark to assess a person's maturity, unlike Dawan customary law, which does not set a specific age but has its own evaluation adjusted to their social order and way of life as Dawan indigenous people. The issues addressed in this journal are: (1) What are the criteria for adulthood for an individual according to Dawan customary law? And (2) What is the process of maturation according to Dawan customary law? This research is empirical, involving observations of the various patterns of life within Dawan society. Data processing is conducted through various identification and analysis methods, leading to conclusions. The results of this study indicate that the criteria for adulthood according to Dawan customary law can be seen through three provisions: assessed based on an individual's biological growth, evaluated based on their ability to perform certain activities, and judged by changes in behavior. The determination of maturity for both males and females are differentiated according to their social order.